Higher Education Policy in Bangladesh: A Philosophical and Practitioner’s Perspective on Initiation, Formulation, and Implementation - Pervin, Nasrin (CV. Gerasi Insan Nusantara, 2025)
This paper analyzes the dynamics of initiation, formulation, and implementation of policy processes within the scope of higher education policy of Bangladesh, particularly relating to the narratives of “quality.” It draws from policy and education sociology to illuminate the specific political, socio-economic, and ideological factors that influence policy gap agendas. The study contextualizes Bangladesh's higher education policy within global and domestic frameworks, illustrating the global forces, the influence of donors, and the market-oriented reforms, along with the local political ideologies and the bureaucratic frameworks. While the policy text captures the desires for decentralization, democracy, modernization, and the global knowledge economy, the policymaking processes, and implementation reveal contradictions, exclusions, and bounded reflexivity. The analysis emphasizes that “quality” is usually unmeasurable and remains a mediated and constructed term by state and policy actors, devoid of a concrete reform framework. The paper illustrates the relentless pursuit of political interests, economic forces, and stagnation of institutional change in Bangladesh that makes the endeavor for reforming higher education system unsustainable and inequitable.